Implikasi Filsafat Ilmu dan Etika Keilmuan dalam Pengembangan Ilmu Pengetahuan Modern - Muh Irfhan Muktapa (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2021)
The development of science also accompanies the development of modern society. Science that develops and brings changes to humans that causes problems from material aspects to mental aspects. The rapid development of modern science and technology takes into account the aspects of systems, values, values ​​and religious values, so that moral degradation has emerged. The purpose of this research is to examine the implications of the philosophy of science in the development of modern scientific ethics. The method used in this research is literature study. The discussion analysis shows that the philosophy of science must be integrated philosophically in order to realize scientific functions, especially in moral, intellectual and social aspects. This is because science is neutral and disagrees with good or bad, considering that it is science who has the right to determine the attitude. Utilization of science for human settlement in the operations of the owner of knowledge and its contribution to the problems of human life. As science develops, it is the philosophy of science that plays a role in realizing good scientific ethics. The existence of the philosophy of science aims to restore science in order to continue to encourage people to think and behave wisely and wisely.